1997
DOI: 10.1109/94.625648
|View full text |Cite
|
Sign up to set email alerts
|

Charge distribution and transport in polymers

Abstract: Experimental work on charge distributions and charge transport in polymer films is reviewed. For studying the charge distributions in the thickness dimension, thermal or acoustic techniques are used with resolutions down to N 1 pm. The polymer samples usually are charged with corona, electron beam or thermal methods. Observation of the change of charge and polarization distributions with time allows one to draw conclusions about charge transport and charge injection phenomena. In some cases theoretical models … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
42
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(44 citation statements)
references
References 111 publications
2
42
0
Order By: Relevance
“…It is generally concluded that such space charge may result from electrons (and holes) injection from the electrodes and electric field assisted ionization of the impurities in the material or from an inhomogeneous polarization [4][5][6][7][8][9][10]. With the success of space charge measurement on the film samples, attempts had also been made to apply the same techniques (mostly the PEA) in extruded polymer insulated power cables to study the space charge behaviour in cable geometry [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…It is generally concluded that such space charge may result from electrons (and holes) injection from the electrodes and electric field assisted ionization of the impurities in the material or from an inhomogeneous polarization [4][5][6][7][8][9][10]. With the success of space charge measurement on the film samples, attempts had also been made to apply the same techniques (mostly the PEA) in extruded polymer insulated power cables to study the space charge behaviour in cable geometry [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…FERROELECTRET is a thin and flexible cellular polymer foam that can store charges in its internal voids [1][2][3][4], thus being able to generate electric pulse under mechanical deformation such as compression and bending [5][6]. Due to its high piezoelectric voltage constant g 33 [7], ferroelectret has already been used extensively in sensor applications, such as blood pressure pulse transducer [8], touch sensor [9], ultrasonic transducer [10], prosthetic skin [11], and accelerometer [12].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the space charge accumulation and the related trapping-detrapping phenomena are still poorly understood. Over recent decades, a great deal of effort has been expended in developing experimental tools for space charge characterization, 2-6 in measuring space charges profiles, [7][8][9] or in identifying the different kinds of charges. 10,11 Meanwhile, only a few attempts have been made to provide some model description of these experimental results.…”
Section: Introductionmentioning
confidence: 99%